Glass antistatic protective film and preparation method thereof
By using sustained release microspheres composed of antistatic agents and hollow mesoporous silica microspheres in the glass antistatic protective film, combined with the lamination of hollow glass microbeads, the problem of antistatic agent loss in the prior art is solved, and long-term antistatic effect is achieved and sound insulation and insulation performance is improved.
Patent Information
- Application Number
- CN202510149905.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-04-18
AI Technical Summary
After long-term use of the existing glass antistatic protective film, antistatic agent will be lost in large quantities, making it difficult to achieve long-term antistatic effect.
The sustained-release microspheres prepared with antistatic agent as the core and hollow mesoporous silica microspheres as the shell are used, combined with polydimethylsiloxane and α-aminosilane coupling agent, hollow glass microbeads and sustained-release microspheres are laid through blow-spray to form a glass antistatic protective film.
It realizes the long-term anti-static effect of the glass anti-static protective film, improves sound insulation and thermal insulation performance, and extends the service life of the anti-static agent.
Smart Images

Figure CN119842107A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of antistatic films, in particular to an antistatic protective film for glass and a preparation method thereof. Background Art
[0002] Antistatic glass is a glass material treated by special technology to remove the static charge on the glass surface, thereby reducing the possibility of static adsorption and electromagnetic interference, and increasing transmittance and optical performance. Antistatic glass is usually obtained by applying a film or coating containing antistatic material to ordinary glass.
[0003] In the prior art, the glass antistatic protective film is usually prepared by spraying an antistatic agent on the surface of a base film, which does have a good antistatic effect in the initial stage, but with a long period of use, the antistatic agent on the base film will be lost in large quantities, making it difficult to achieve a long-term antistatic effect. Based on this, a glass antistatic protective film and a preparation method thereof are proposed. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a glass antistatic protective film and a preparation method thereof, wherein sustained-release microspheres are prepared with an antistatic agent as the core and hollow mesoporous silica microspheres as the shell, so that the protective film can achieve a long-lasting antistatic effect.
[0005] To achieve the above object, the present invention provides the following technical solution: a glass antistatic protective film, which comprises, from bottom to top, a base film, a base layer, an insulating layer, a connecting layer, an antistatic layer and a consolidation layer;
[0006] The antistatic layer is composed of an antistatic agent and hollow mesoporous silica microspheres;
[0007] The insulating layer is composed of hollow glass microspheres;
[0008] The base layer, the connection layer and the consolidation layer are formed by drying and solidifying the mixed solution.
[0009] Preferably, the base film is selected from PET film and OPP film.
[0010] Preferably, the total thickness of the glass antistatic protective film is 0.12-0.2 mm.
[0011] The present invention also provides a method for preparing an antistatic protective film for glass, comprising the following steps:
[0012] (1) uniformly stirring polydimethylsiloxane and α-aminosilane coupling agent, and then dissolving them in toluene solvent to form a mixed solution;
[0013] (2) coating the mixed solution on the surface of the base film, and spraying the hollow glass microspheres when the base film is dried to semi-solidified, and then coating the mixed solution, and spraying the slow-release microspheres when the base film is dried to semi-solidified;
[0014] (3) The mixed solution is coated on the surface of the sustained-release microspheres, and after drying and solidification, an antistatic protective film for glass is obtained.
[0015] Preferably, in step (1), the mass ratio of the polydimethylsiloxane to the α-aminosilane coupling agent is (10-12):1; the volume ratio of the polydimethylsiloxane to the α-aminosilane coupling agent to the toluene solvent is 1:(8-10).
[0016] Preferably, in step (2), the hollow glass microspheres account for 8-10% of the total mass of the mixed solution; and the sustained-release microspheres account for 10-15% of the total mass of the mixed solution.
[0017] Preferably, in step (2), the size of the hollow glass microspheres is 5-10 μm; the size of the sustained-release microspheres is 200-300 nm.
[0018] Preferably, in step (2), the preparation method of the sustained-release microspheres is as follows: S1, mixing octadecyl dimethyl hydroxyethyl quaternary ammonium sodium nitrate and deionized water to obtain an antistatic liquid; S2, ultrasonically dispersing the hollow mesoporous silica microspheres in the antistatic liquid, filtering and drying, to obtain sustained-release microspheres with an antistatic agent as a core and hollow mesoporous silica microspheres as a shell.
[0019] Preferably, in step S1, the volume ratio of the octadecyl dimethyl hydroxyethyl quaternary ammonium sodium nitrate and deionized water is (2-4):1.
[0020] Preferably, in step S2, the material-liquid ratio of the hollow mesoporous silica microspheres to the antistatic liquid is 1:5 g / mL; and the ultrasonic dispersion time is 3-5 h.
[0021] The present invention provides a glass antistatic protective film and a preparation method thereof, which has the following beneficial effects compared with the prior art:
[0022] The present invention uses polydimethylsiloxane and α-aminosilane coupling agent as connecting materials, and adopts a blowing method to stack and lay hollow glass microspheres and slow-release microspheres, thereby ensuring uniform dispersion and laying of the hollow glass microspheres and slow-release microspheres, and improving the sound insulation and heat preservation performance of the glass antistatic protective film.
[0023] The invention uses an antistatic agent as a core and hollow mesoporous silica microspheres as a shell to prepare slow-release microspheres, so that the antistatic agent is slowly released from the hollow mesoporous silica microspheres, allowing the protective film to achieve a long-lasting antistatic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0025] Figure 1 This is a schematic diagram of the structure of the glass antistatic protective film of the present invention;
[0026] Figure 2 This is a morphology diagram of the antistatic layer in Example 3 of the present invention. DETAILED DESCRIPTION
[0027] The following examples are used to explain the implementation methods of the present application in detail, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.
[0028] Example 1
[0029] The preparation method of sustained-release microspheres is as follows:
[0030] S1. Mix octadecyl dimethyl hydroxyethyl quaternary ammonium sodium nitrate and deionized water in a volume ratio of 2:1 to obtain an antistatic liquid;
[0031] S2. The hollow mesoporous silica microspheres are dispersed in an antistatic liquid by ultrasonic for 3 h at a material-liquid ratio of 1:5 g / mL. After filtering and drying, sustained-release microspheres with an antistatic agent as a core and hollow mesoporous silica microspheres as a shell are prepared.
[0032] Example 2
[0033] The preparation method of sustained-release microspheres is as follows:
[0034] S1. Mix octadecyl dimethyl hydroxyethyl quaternary ammonium sodium nitrate and deionized water in a volume ratio of 4:1 to obtain an antistatic liquid;
[0035] S2. The hollow mesoporous silica microspheres are dispersed in an antistatic liquid by ultrasonic for 5 h at a material-liquid ratio of 1:5 g / mL. After filtering and drying, sustained-release microspheres with an antistatic agent as a core and hollow mesoporous silica microspheres as a shell are prepared.
[0036] Example 3
[0037] The preparation method of sustained-release microspheres is as follows:
[0038] S1. Mix octadecyl dimethyl hydroxyethyl quaternary ammonium sodium nitrate and deionized water in a volume ratio of 3:1 to obtain an antistatic liquid;
[0039] S2. The hollow mesoporous silica microspheres are dispersed in an antistatic liquid by ultrasonic for 4 hours at a material-liquid ratio of 1:5 g / mL. After filtering and drying, sustained-release microspheres with an antistatic agent as a core and hollow mesoporous silica microspheres as a shell are prepared.
[0040] Example 4
[0041] A glass antistatic protective film comprises, from bottom to top, a base film, a base layer, an insulating layer, a connecting layer, an antistatic layer and a consolidation layer; the antistatic layer is composed of an antistatic agent and hollow mesoporous silica microspheres; the insulating layer is composed of hollow glass microspheres; the base layer, the connecting layer and the consolidation layer are formed by drying and curing a mixed solution. The base film is selected from an OPP film. The total thickness of the glass antistatic protective film is 0.12 mm.
[0042] The method for preparing the above-mentioned glass antistatic protective film comprises the following steps:
[0043] (1) uniformly stirring polydimethylsiloxane and α-aminosilane coupling agent at a mass ratio of 12:1, and then dissolving them in a toluene solvent at a volume ratio of 1:8 to form a mixed solution;
[0044] (2) coating the mixed solution on the surface of the base film, and spraying hollow glass microspheres (size of 5-10 μm) when the mixed solution is dried to semi-solidified, and then coating the mixed solution again, and spraying slow-release microspheres (size of 200-300 nm) when the mixed solution is dried to semi-solidified;
[0045] The hollow glass microspheres account for 10% of the total mass of the mixed solution; and the sustained-release microspheres account for 10% of the total mass of the mixed solution.
[0046] (3) The mixed solution is coated on the surface of the sustained-release microspheres, and after drying and solidification, an antistatic protective film for glass is obtained.
[0047] In this example, the sustained-release microspheres in Example 1 were used.
[0048] Example 5
[0049] A glass antistatic protective film comprises, from bottom to top, a base film, a base layer, an insulating layer, a connecting layer, an antistatic layer and a consolidation layer; the antistatic layer is composed of an antistatic agent and hollow mesoporous silica microspheres; the insulating layer is composed of hollow glass microspheres; the base layer, the connecting layer and the consolidation layer are formed by drying and curing a mixed solution. The base film is selected from a PET film. The total thickness of the glass antistatic protective film is 0.2 mm.
[0050] The method for preparing the above-mentioned glass antistatic protective film comprises the following steps:
[0051] (1) uniformly stirring polydimethylsiloxane and α-aminosilane coupling agent at a mass ratio of 10:1, and then dissolving them in a toluene solvent at a volume ratio of 1:10 to form a mixed solution;
[0052] (2) coating the mixed solution on the surface of the base film, and spraying hollow glass microspheres (size of 5-10 μm) when the mixed solution is dried to semi-solidified, and then coating the mixed solution again, and spraying slow-release microspheres (size of 200-300 nm) when the mixed solution is dried to semi-solidified;
[0053] The hollow glass microspheres account for 8% of the total mass of the mixed solution; the sustained-release microspheres account for 15% of the total mass of the mixed solution.
[0054] (3) The mixed solution is coated on the surface of the sustained-release microspheres, and after drying and solidification, an antistatic protective film for glass is obtained.
[0055] In this embodiment, the sustained-release microspheres in Example 2 were used.
[0056] Example 6
[0057] A glass antistatic protective film comprises, from bottom to top, a base film, a base layer, an insulating layer, a connecting layer, an antistatic layer and a consolidation layer; the antistatic layer is composed of an antistatic agent and hollow mesoporous silica microspheres; the insulating layer is composed of hollow glass microspheres; the base layer, the connecting layer and the consolidation layer are formed by drying and curing a mixed solution. The base film is selected from a PET film. The total thickness of the glass antistatic protective film is 0.2 mm.
[0058] The method for preparing the above-mentioned glass antistatic protective film comprises the following steps:
[0059] (1) uniformly stirring polydimethylsiloxane and α-aminosilane coupling agent at a mass ratio of 10:1, and then dissolving them in a toluene solvent at a volume ratio of 1:9 to form a mixed solution;
[0060] (2) coating the mixed solution on the surface of the base film, and spraying hollow glass microspheres (size of 5-10 μm) when the mixed solution is dried to semi-solidified, and then coating the mixed solution again, and spraying slow-release microspheres (size of 200-300 nm) when the mixed solution is dried to semi-solidified;
[0061] The hollow glass microspheres account for 10% of the total mass of the mixed solution; and the sustained-release microspheres account for 12% of the total mass of the mixed solution.
[0062] (3) The mixed solution is coated on the surface of the sustained-release microspheres, and after drying and solidification, an antistatic protective film for glass is obtained.
[0063] In this example, the sustained-release microspheres in Example 3 were used.
[0064] Comparative Example 1
[0065] A method for preparing an antistatic protective film for glass comprises the following steps:
[0066] (1) uniformly stirring polydimethylsiloxane and α-aminosilane coupling agent at a mass ratio of 10:1, and then dissolving them in a toluene solvent at a volume ratio of 1:9 to form a mixed solution;
[0067] (2) Hollow glass microspheres (size of 5-10 μm) and sustained-release microspheres (size of 200-300 nm) are placed in a mixed solution and stirred uniformly to obtain a slurry; wherein the hollow glass microspheres account for 10% of the total mass of the mixed solution; and the sustained-release microspheres account for 12% of the total mass of the mixed solution.
[0068] (3) The slurry is coated on the surface of the PET base film, and after drying and curing, a glass antistatic protective film with a thickness of 0.2 mm is obtained.
[0069] Comparative Example 2
[0070] A method for preparing an antistatic protective film for glass comprises the following steps:
[0071] (1) uniformly stirring polydimethylsiloxane and α-aminosilane coupling agent at a mass ratio of 10:1, and then dissolving them in a toluene solvent at a volume ratio of 1:9 to form a mixed solution;
[0072] (2) coating the mixed solution on the surface of the PET base film, and spraying hollow glass microbeads (size 5-10 μm) when the mixed solution is dried to semi-solidified, and then coating the mixed solution, and spraying an antistatic agent (octadecyl dimethyl hydroxyethyl quaternary ammonium sodium nitrate) after the mixed solution is dried to semi-solidified;
[0073] The hollow glass microspheres account for 10% of the total mass of the mixed solution; the antistatic agent accounts for 0.5% of the total mass of the mixed solution.
[0074] (3) After drying and curing, a glass antistatic protective film with a thickness of 0.2 mm is obtained.
[0075] Quality Inspection
[0076] 1. The glass antistatic protective films in Examples 4-6 and Comparative Examples 1-2 were used as test objects. The sound insulation effect was tested in accordance with the standard of GB / T18696, specifically in a noise environment with a sound pressure level of 90 dB and a frequency range of 100-3150 Hz; the thermal insulation was tested in accordance with the standard of ASTME1461. The specific results are shown in the following table.
[0077] Table 1 Sound insulation and thermal insulation
[0078] category Sound insulation, dB Thermal insulation, w / (m·K) Example 4 48.3 0.122 Example 5 51.7 0.114 Example 6 52.2 0.108 Comparative Example 1 50.1 0.117 Comparative Example 2 50.5 0.121 0.2mm PET film 22.3 0.245
[0079] It can be seen from the above table that compared with Example 6, the sound insulation and thermal insulation of the glass antistatic protective film in Comparative Example 1 are slightly reduced, indicating that the hollow glass microspheres and slow-release microspheres are difficult to be evenly dispersed into the mixed solution when direct mixing is used, thus affecting the quality of the glass antistatic protective film.
[0080] 2. The glass antistatic protective films in Example 6 and Comparative Example 2 were used as test objects. The surface resistivity was tested according to the standard of GB / T1410-2006, and then the surfaces were scrubbed with water 100 times, left to stand for 24 hours, and the surface resistivity was tested again. The specific results are shown in the following table.
[0081] Table 2 Antistatic properties
[0082] category Surface resistance / Ω Scrub 100 times Surface resistance / Ω Example 6 <![CDATA[4.3×10 6 ]]> <![CDATA[3.4×10 6 ]]> Comparative Example 2 <![CDATA[4.0×10 6 ]]> <![CDATA[1.2×10 8 ]]>
[0083] It can be seen from the above table that the initial antistatic performance of the glass antistatic protective film in Example 6 and Comparative Example 2 is similar; after repeated scrubbing, the antistatic performance of the glass antistatic protective film in Comparative Example 2 is greatly reduced, but the antistatic performance of the glass antistatic protective film in Example 6 is still good, indicating that the use of sustained-release microspheres can indeed ensure the durability of the antistatic property of the protective film.
[0084] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A glass antistatic protective film, characterized in that: From bottom to top, it includes a base film, a base layer, an isolation layer, a connecting layer, an antistatic layer and a consolidation layer; The antistatic layer is composed of an antistatic agent and hollow mesoporous silica microspheres; The insulating layer is composed of hollow glass microspheres; The base layer, the connection layer and the consolidation layer are formed by drying and solidifying the mixed solution.
2. The glass antistatic protective film according to claim 1, characterized in that: The base film is selected from PET film and OPP film.
3. The glass antistatic protective film according to claim 1, characterized in that: The total thickness of the glass antistatic protective film is 0.12-0.2 mm.
4. The method for preparing the glass antistatic protective film according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) uniformly stirring polydimethylsiloxane and α-aminosilane coupling agent, and then dissolving them in toluene solvent to form a mixed solution; (2) coating the mixed solution on the surface of the base film, and spraying the hollow glass microspheres when the base film is dried to semi-solidified, and then coating the mixed solution, and spraying the slow-release microspheres when the base film is dried to semi-solidified; (3) The mixed solution is coated on the surface of the sustained-release microspheres, and after drying and solidification, an antistatic protective film for glass is obtained.
5. The method for preparing the glass antistatic protective film according to claim 4, characterized in that: In step (1), the mass ratio of the polydimethylsiloxane to the α-aminosilane coupling agent is (10-12):1; the volume ratio of the polydimethylsiloxane to the α-aminosilane coupling agent to the toluene solvent is 1:(8-10).
6. The method for preparing the glass antistatic protective film according to claim 4, characterized in that: In step (2), the hollow glass microspheres account for 8-10% of the total mass of the mixed solution; and the sustained-release microspheres account for 10-15% of the total mass of the mixed solution.
7. The method for preparing the glass antistatic protective film according to claim 4, characterized in that: In step (2), the size of the hollow glass microspheres is 5-10 μm; the size of the sustained-release microspheres is 200-300 nm.
8. The method for preparing the glass antistatic protective film according to claim 4, characterized in that: In step (2), the preparation method of the sustained-release microspheres is as follows: S1, mixing octadecyl dimethyl hydroxyethyl quaternary ammonium sodium nitrate and deionized water to obtain an antistatic liquid; S2. Ultrasonic dispersion of hollow mesoporous silica microspheres in antistatic liquid, filtering and air-drying to obtain sustained-release microspheres with an antistatic agent as a core and hollow mesoporous silica microspheres as a shell.
9. The method for preparing the glass antistatic protective film according to claim 8, characterized in that: In step S1, the volume ratio of the octadecyl dimethyl hydroxyethyl quaternary ammonium sodium nitrate and deionized water is (2-4):
1.
10. The method for preparing the glass antistatic protective film according to claim 8, characterized in that: In step S2, the material-liquid ratio of the hollow mesoporous silica microspheres to the antistatic liquid is 1:5 g / mL; and the ultrasonic dispersion time is 3-5 h.